Circadian variation and seasonal distribution of implantable defibrillator detected new onset atrial fibrillation. Issue 12 (15th September 2020) - Younis, Arwa; Goldenberg, Ilan; McNitt, Scott; Kutyifa, Valentina; Polonsky, Bronislava; Goldenberg, Ido; Zareba, Wojciech; Aktas, Mehmet K.
Abstract: Background: We aimed to characterize the hourly, daily, and seasonally variations in the detection of new atrial fibrillation (AF) in heart failure patients implanted with a defibrillator. Methods: In 1309 patients enrolled in MADIT‐RIT without AF at baseline, atrial arrhythmia data were analyzed from device interrogations. The circadian, weekly, and seasonal distribution of device detected AF was evaluated. The morning period was defined as 06:00‐11:59, afternoon as 12:00‐16:59, evening as 17:00‐22:59, and the nighttime as 23:00‐05:59. Results: During 17 months of follow‐up, 66 (5%) patients developed new device‐detected AF. AF patients were less likely to have ischemic cardiomyopathy and were more likely to have received an implantable cardioverter defibrillator rather than a cardiac resynchronization therapy with defibrillator. The highest number of AF occurred during the evening hours (25 patients [38%]) followed by a second peak in AF detection during the afternoon hours (21 patients [32%]). Importantly during the nighttime, new AF occurred only in three patients (4%). In comparison with the nighttime period, the odds ratio (OR) of developing AF during the evening time period was 8.5‐fold higher (95% CI 7.3‐9.7, P  < .01). Detection of AF during the spring and winter seasons accounted for 67% of all new device‐detected AF. Conclusions: There is diurnal and seasonal variation in new onset AF. A double peak in the incidence of AF is observed during the afternoon and evening hours, and during the spring and winter seasons. This information may be useful when deciding when to screen at‐risk patients for new AF.